Proteomics and bioinformatics analysis of cardiovascular related proteins in offspring exposed to gestational diabetes mellitus - Pan, Hai-Tao; Xiong, Yi-Meng; Zhu, Hong-Dan; Shi, Xiao-Liang; Yu, Bin; Ding, Hai-Gang; Xu, Ren-Jie; Ding, Jin-Long; Zhang, Tao; Zhang, Juan (Frontiers in Cardiovascular Medicine, 2022)
Previous studies have demonstrated that exposed to the initial suboptimal intrauterine environment of gestational diabetes mellitus (GDM) may increase risk of cardiovascular disease in adulthood. In order to investigate the underlying mechanisms involved in the increased risk of cardiovascular diseases in the offspring of GDM, we applied a high-throughput proteomics approach to compare the proteomic expression profile of human umbilical vessels of normal and GDM offspring. A total of significantly different 100 proteins were identified in umbilical vessels from GDM group compared with normal controls, among which 31 proteins were up-regulated, while 69 proteins were down-regulated. Differentially expressed proteins (DEPs) are validated using Western blotting analysis. The analysis of these differently expressed proteins (DEPs) related diseases and functions results, performed by Ingenuity Pathway Analysis (IPA) software. Based on 'Diseases and Disorders' analysis, 17 proteins (ACTA2, ADAR, CBFB, DDAH1, FBN1, FGA, FGB, FGG, GLS, GSTM1, HBB, PGM3, PPP1R13L, S100A8, SLC12A4, TPP2, VCAN) were described to be associated with Cardiovascular disease, especially in Anemia, Thrombus and Myocardial infarction. Functional analysis indicated that DEPs involved in many cardiovascular functions, especially in 'vasoconstriction of blood vessel' (related DEPs: ACTA2, DDAH1, FBN1, FGA, FGB and FGG). Upstream regulator analyses of DEPs identifies STAT3 as inhibitor of ACTA2, FGA, FGB and FGG. The results of this study indicate that intrauterine hyperglycemia is associated with an elevated risk of cardiovascular risk in the offspring.